KESESUAIAN KAWASAN PERDAGANGAN KOTA SERANG MENGGUNAKAN METODE SPATIAL MULTICRITERIA EVALUATION - Pradono, Kuncoro Adi; Wibowo, Adi; Veronica, Kiki Winda (J SIG (Jurnal Sains Informasi Geografi), 2024)
An open source geographic information system (GIS) can assist stakeholders in assessing the suitability of trade areas to support economic growth and sustainable development. Serang City as the capital of Banten Province from the expansion of West Java Province is a developing area, one of which is a new trade center. The spatial multicriteria evaluation (SMCE) method, one of the features of ILWIS, is used to evaluate the suitability of trade areas in Serang City. The factors considered in evaluating the suitability of trade areas are zonation, accessibility, and visibility. Through the results of SMCE analysis, as much as 16% or about 4000 hectares are suitable for trade areas, most of which are scattered in the city center, while 80% are not suitable if they are intended for trade areas.  Serang and Taktakan sub-districts are the most suitable areas, while Kasemen sub-district is generally unsuitable. This is still in line with the RTRW 2008-2030. The open source-based software in this study effectively performs SMCE analysis. This study is expected to provide a reference for the relevant government, stakeholders and investors to develop a sustainable trade area in Serang City.